The effects of circuit-based resistance training on blood pressure, arterial stiffness, and body composition in community-dwelling older adults: a systematic review and meta-analysis - Hu, Zhongxu; Jiang, Shihua; Hu, Chenhao; Shen, Boao; Gu, Jinfa (Frontiers in Physiology, 2025)
BackgroundThe global aging population has led to a public health crisis, with cardiovascular disease, hypertension, arterial stiffness, and obesity becoming major concerns. Resistance training (RT) has been shown to improve cardiovascular health, but traditional RT has certain limitations.Objective and data sourcesThe present systematic review and meta-analysis aims to assess the effects of circuit-based resistance training (CBRT) on blood pressure, arterial stiffness as well as body composition in community-dwelling older adults. PubMed, Cochrane library, Embase, Scopus, and Web of Science, five databases in total, were searched until January 2025. The analysis was restricted to randomized controlled trials.MethodsA total of 14 studies, involving 704 participants, were included in the meta-analysis. The primary outcomes assessed were arterial stiffness, blood pressure, and body composition.ResultsSignificant intervention effects were identified in systolic blood pressure (WMD = −6.10 mmHg, 95% CI: −8.07 to −4.12), diastolic blood pressure (WMD = −2.88 mmHg, 95% CI: −3.96 to −1.81), brachial-ankle pulse wave velocity (WMD = −101.81 cm/s, 95% CI: −136.92 to −66.70), percentage of body fat (WMD = −3.21%, 95% CI: −4.20 to −2.22), fat mass (WMD = −4.83 kg, 95% CI: −8.80 to −0.86), lean body mass (WMD = 1.36 kg, 95% CI: 0.83–1.89), and femoral neck bone mineral content (WMD = 0.27 g, 95% CI: 0.14–0.39). Subgroup analysis by training frequency showed that participants with high training frequency (>3 sessions/week) reduce systolic blood pressure more significantly compared to moderate to low training frequency (≤2 sessions/week) while diastolic blood pressure show no difference between subgroups.ConclusionCBRT interventions improve blood pressure, arterial stiffness, and body composition in community-dwelling older adults significantly. Additionally, three sessions of CBRT per week show a superior systolic blood pressure lowering effect.Systematic Review RegistrationPROSPERO, identifier CRD42025646360.